Efficient technique for broadband monostatic RCS using the characteristic basis function method with polynomial interpolation. Issue 14 (1st July 2017) - Chen, Xinlei; Fei, Chao; Gu, Changqing; Mittra, Raj
Abstract : Previous research on the characteristic basis function method (CBFM) has shown that the use of the ultra‐wide band CBFM can efficiently solve the problem of computing the broadband monostatic radar cross‐section (RCS) of a target by reducing the size of the associated impedance matrix and avoiding the repeated generation of the macro base functions. However, it is still necessary to repeatedly construct the reduced matrix at each frequency in the analysed frequency band, and an interpolation method is proposed to address this problem. It is shown that it is only needed to generate and store the reduced matrices at four frequency samples to cover the entire frequency band, and efficiently derive the reduced matrices at other frequencies via simple interpolation. Numerical results are given to demonstrate the accuracy and efficiency of the proposed method.